Microbiota of the ocular surface in infectious/ inflammatory eye diseases - M. M. Bikbov; O. I. Orenburkina; A. E. Babushkin (Российский офтальмологический журнал, 2024)
The review article presents current data on the microbiota (MBT) of the ocular surface in infectious and inflammatory eye diseases. Saprophytic MBT increases the resistance of the ocular surface to pathogenic bacteria. Commensal microorganisms regulate host metabolism, immune system development, and defense of the host against pathogen invasion. Meanwhile, ocular surfaces can change due to various environmental factors, processes in the human body, and in particular, due to ophthalmological diseases. Damaged epithelium of the cornea and conjunctiva (e. g. caused by dryness, the use of contact lenses, antibiotics, etc.) can lead to an increase in the number of bacteria on the ocular surface and disruption of the protective film containing antimicrobial compounds that lubricates the epithelium. In recent years, a connection has been shown between changes in the composition of the ocular MBT and a number of infectious and inflammatory ophthalmological diseases. In particular, it turned out that factors influencing the formation of tear fluid can change the MBT of the ocular surface, and when its composition deteriorates, ocular surface may become dry. An increase in the number of pathogenic microorganisms when wearing contact lenses, especially gram-negative ones, can lead to changes in the MBT and the development of keratitis. In inflammatory eye diseases, gram-positive microflora is most often isolated (in 94 % of cases), of which coagulaze negative staphylococci are most often recorded. In bacterial eye infections. conditionally pathogenic microflora often occurs (44.5 %). Apparently, intestinal MBT plays a very significant role in the development of some inflammatory eye diseases such as anterior and posterior uveitis.